READING GROUPS AS SPACES OF LEARNING AND RESISTANCE: CARE EMOTIONS AND FEMINISM IN EAP (BALEAP Journal of Research and Practice, 2025)
Care, emotions and feminism are critical concepts in the English for Academic Purposes (EAP) landscape. However, to date they have existed largely on the periphery, seldom given equal standing alongside more traditional EAP areas of focus. Recognizing the need for change, this article is the result of a dialogic inquiry of four female academics from different UK Higher education institutions who met via a conference reading group foregrounding these topics at the 2023 BALEAP conference.   Our investigation explored the role of reading groups in our professional practice and development. In particular, their potential as ‘counter-sites’ (Foucault, 1986) or spaces of radical possibility for self-directed learning, community building and resistance to increasing encroachment on academic autonomy and the commercialisation of academic labour. Underpinning our reflections and dialogues were three pivotal texts selected for this conference reading session. These explored care as a central academic value (Tuck, 2018), emotions as activism (Benesch, 2020), and the ‘disruptive potential’ of feminism (Cerdá, 2020: 216). As discussion lies at the heart of any reading group, we adopted a methodology which centres dialogue and polyvocality, allowing for the researchers’ individual voices to be heard and seen: duoethnography (Sawyer & Norris, 2013). Accordingly, we present our inquiry as duoethnographers often do (e.g., Lowe and Lawrence, 2020), via scripted dialogues.   The analysis is organised into four thematic sections, positioned as ‘stepping stones’: socialisation into EAP, developing as an EAP practitioner, gendered experiences: tensions and power struggles, and community, belonging and finding a home. Each section begins with a brief introduction and concludes with a reflective summary to guide the reader. The dialogues, however, are the core elements of the write-up, designed to engage the reader in an ongoing conversation, prompting reflection on personal experiences and understandings.   We invite you, the reader, to join this conversation. Reflecting on and sharing your own insights will bring discussions around care, emotions and feminism to the fore. We believe this meaningful development and expansion of core EAP discourses will enrich our professional and academic community for all.